WS2/WO3 modified carbon anode as efficient electrocatalysts for enhancing electricity generation and pollution removal - Sang, Yugang; Jiang, Quantong; Guan, Fang; Wang, Nan; Etim, Ini-Ibehe Nabuk; Fan, Keliang; Duan, Jizhou (Frontiers in Microbiology, 2025)
Microbial fuel cells (MFCs) have emerged as a new energy technology to solve severe energy and environmental issues. As a bridge connecting the internal and external circuits and a habitat for microorganisms, the anode is a key component influencing the performance output of MFCs. Recently, tungsten trioxide (WO3) and tungsten disulfide (WS2) can be used for the MFC setup. In this study, a direct hydrothermal synthesis method was employed to prepare WS2/WO3 nanomaterials. It was subsequently integrated with carbon paper (CP) to develop WS2/WO3-CP and WO3-CP anodes for MFCs. Contact angle tests showed that the hydrophilicity of the WS2/WO3-CP electrode was significantly improved. In electrochemical tests, the MFCs with WS2/WO3-CP anode exhibited lower charge transfer resistance and higher electron transfer efficiency than the original ones. The MFC with the WS2/WO3-CP anode had a maximum power density reaching 2.32 W·m−2, which was 1.34 and 3.09 times higher than that of the WO3-CP and bare CP anodes, respectively. Meanwhile, this MFC with the WS2/WO3-CP anode showed higher removal rates of chemical oxygen demand and SO42− than the WO3-CP and CP anodes. The modified WS2/WO3 nanomaterials are promising materials that can be adopted for MFCs industrial use.